A Study On Database Structure Of Prosumer System For Online Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Energy prosumer can not only save on electrical bills but also make profits by selling energy produced.  To develop online prosumer platform, this paper present database structure of each prosumer system(Photovoltaic system, Energy Storage System, Wind power system, EV Charger system). The cause of abnormalities in prosumer facilities and designed the database and developed the reference model by big data measured from the hardware. The data was preprocessed all values from the acquired data between 0 and 1 and training set and test set generated for the data transposition process. For applied AI algorithms, this paper adapted DNN(Deep Neural Network) method. This paper used Precision, Recall, Accuracy, F1-score. The result of experiment is high value of each expression. Recall value is high values and this expression is important to safety area focus. This database structure will provide online prosumer platform system and batter prediction safety system.